PENGARUH DOSIS PUPUK MIKORIZA VESICULAR ARBUSKULAR TERHADAP SIFAT KIMIA TANAH PADA TANAMAN KEDELAI (Glycine max (L) Merr) - Julianus Jeksen (Agriculture Faculty of Flores University, 2012)
This study aims at determining the influence of vesicular-arbuscular mycorrhiza dosage on soil chemical properties of soybean and its optimum dosage that can increase the soil available-P on crops of soybean. This research was conducted in Lokoboko village, Ndona Subdistrict of Ende regency. This study used Randomized Block Design and a single-pattern factor consists of five treatments and four replications namely M0 : 0 gr pot-1 or without mycorrhiza, M5: 5 gr pot-1 mycorrhiza, M10: 10 gr pot-1 mycorrhiza, M15: 15 gr pot-1 mycorrhiza and M20: 20 gr pot-1 mycorrhiza. The variables of this study are plant–absorption P (mg tan-1), soil–available P (mg kg-1), soil-organic C (%) and pH of soil. The results showed that the use of vesicular-arbuscular mycorrhiza fertilizer for crops of soybean could increase soil-available P in 56,26%, plant-absorption P in 65%, pH of the soil in 6,06% and soil-organic C in 62,68 %. The use of vesicular-arbuscular mycorrhiza fertilizer on the dosage of 20 g has the better effectivity in increasing soil-available P in the soybean plant.